2021
DOI: 10.1101/2021.10.06.463315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale comparative genomics unravels great genomic diversity across the Rickettsia and Ca. Megaira genera and identifies Torix group as an evolutionarily distinct clade

Abstract: Rickettsia are intracellular bacteria originally described as arthropod borne pathogens that are emerging as a diverse group of often biologically important, non-pathogenic symbionts of invertebrates and microeukaryotes. However, sparse genomic resources for symbiotic strains and for the sister genus (Candidatus Megaira) inhibit our understanding of Rickettsia evolution and biology. Here, we present the first closed genomes of Ca. Megaira from an alga (Mesostigma viride), and Torix Rickettsia from midge (Culic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Previous studies have delimited multiple cif clades denominated as Type I to IV and a proposed Type V comprising homologues carrying additional domains on the C-terminal part of the cifB protein. cif homologues have also been reported in other Rickettsiales , some of them carried by plasmids (Gillespie et al 2018; Davison et al 2021; Martinez et al 2021; Takano et al 2021). We investigated the evolutionary origin of the cif genes located on Wolbachia -associated plasmid sequences and found that they group with Type V homologues (Figure 6), which is consistent with the length and predicted domains of their cifB protein (Figure 5).…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies have delimited multiple cif clades denominated as Type I to IV and a proposed Type V comprising homologues carrying additional domains on the C-terminal part of the cifB protein. cif homologues have also been reported in other Rickettsiales , some of them carried by plasmids (Gillespie et al 2018; Davison et al 2021; Martinez et al 2021; Takano et al 2021). We investigated the evolutionary origin of the cif genes located on Wolbachia -associated plasmid sequences and found that they group with Type V homologues (Figure 6), which is consistent with the length and predicted domains of their cifB protein (Figure 5).…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies have delimited multiple cif clades denominated as Type I to IV and a proposed Type V comprising homologues carrying additional domains on the C-terminal part of the cifB protein. cif homologues have also been reported in other Rickettsiales , some of them carried by plasmids [ 33 , 34 , 48 , 49 ]. We investigated the evolutionary origin of the cif genes located on Wolbachia -associated plasmid sequences and found that they group with Type V homologues ( Fig 6 ), which is consistent with the length and predicted domains of their cifB protein ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 99%